Utilization of Biopsy-Guided CT Scan in Diagnosing Liver Cancer: A Case Study - Susanti, Cindy; Agnes Mariska (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Liver cancer is one of the most common types of cancer in Indonesia and has a high mortality rate. Early diagnosis of liver cancer is very important to increase the patient's chances of recovery. Biopsy-guided CT scan is an effective method for diagnosing liver cancer. Case presentation: We report the case of a 55 year old man with a history of chronic hepatitis B who presented with complaints of right upper abdominal pain and weight loss. Physical examination revealed hepatomegaly and ascites. Investigations, including abdominal ultrasound and liver function tests, showed a mass in the liver. CT scan of the abdomen with contrast showed a hypodense mass in the right hepatic lobe. A CT-guided liver biopsy was performed and the histopathological diagnosis was hepatocellular carcinoma (HCC). The patient then underwent partial resection hepatectomy and chemotherapy. Conclusion: Biopsy-guided CT scan is a valuable tool for the diagnosis of HCC in patients with chronic hepatitis B.